A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - Sharrock, R.A.; Sinclair, Fergus L.; Gliddon, C.; Rao, Idupulapati M.; Barrios, Edmundo; Mustonen, P.J.; Smithson, P.; Jones, D.L.; Godbold, D.L. (Springer, 2004)
Tithonia diversifolia (Mexican sunflower) is a shrub commonly used as a green manure crop in Central and South America, Asia and Africa as it accumulates high levels of phosphorus and other nutrients, even in depleted soils. In root samples collected from the global distribution of Tithonia, we examined the degree of mycorrhizal colonisation and estimated the families of associated arbuscular mycorrhizal (AM) fungi. No colonisation by ectomycorrhizas was found. The degree of colonisation by AM fungi was on average 40%, but ranged between 0 and 80%. No mycorrhizal colonisation was found in the samples collected from the Philippines or in one each of the Rwandan and Venezuelan samples. Throughout its global distribution (Costa Rica, Nicaragua, Indonesia, Honduras, Mexico, Kenya and Rwanda), Tithonia forms mainly associations with Glomaceae. Only in one location in Nicaragua were associations with another family (Acaulosporaceae) found.